Digital Communication Strategies in Building Online Communities: A Case Study in Remote Work Communities (KKR) - Zaky Al Hamzah; Fitria Ayuningtyas; Munadhil Abdul Muqsith (Publikasi Indonesia, 2024)
Komunitas Kerja Remote, or Remote Work Community (KKR), is a community of remote workers, freelancers, and solopreneurs in Indonesia. They actively establish communication to learn together and share information, insights, and experiences while networking and informing about remote job openings on the KKR website, namely www.kamikerjaremote.com. The purpose of the research is to study the communication strategy of the remote work community in Indonesia and convey information on remote job openings to all KKR members in Indonesia. The theory used is group synergy, based on research concepts about group communication, group behaviour, and communication patterns. This research uses a descriptive qualitative method with data acquisition by interview method and documentation sources. The results of the research approach are useful for exploring rich and contextual information and supporting an in-depth interpretation of community reality. So KKR's communication strategy in online communication to establish strengthening and remote job vacancy information has been successful. This can be seen from the activation of KKR members in discussing, exchanging ideas, sharing information, insights, and work experiences as remote workers, as well as the increasing number of job openings on the KKR website.